2016
DOI: 10.1177/1087054714548031
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Personality Assessment Inventory for Detecting Malingered ADHD in College Students

Abstract: Individuals who were asked to simulate ADHD easily manipulate the PAI; however, alternative cutoff scores proposed for PAI validity indices may improve the detection of feigned ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…In some studies, the target condition was adjusted to students by using diagnoses more familiar to them, such as ADHD (e.g. Musso et al, 2016). Other studies investigated the influence of different student-related benefits on the way students fabricate the ADHD claims (e.g.…”
Section: Do Motives Matter? a Comparison Between Positive And Negative Incentives In Students' Willingness To Malingermentioning
confidence: 99%
“…In some studies, the target condition was adjusted to students by using diagnoses more familiar to them, such as ADHD (e.g. Musso et al, 2016). Other studies investigated the influence of different student-related benefits on the way students fabricate the ADHD claims (e.g.…”
Section: Do Motives Matter? a Comparison Between Positive And Negative Incentives In Students' Willingness To Malingermentioning
confidence: 99%
“…Thus self‐report measures, such as the PAI, may be susceptible to efforts to feign ADHD (Musso, Hill, Barker, Pella, & Gouvier, ). These previous studies have found that the symptoms of ADHD can be easily feigned, especially when symptoms are assessed with self‐report measures (Booksh et al., ; Musso et al., ; Sollman et al., ). Although some of the items on the PAI may appear to have high face validity for ADHD symptoms, this is comparable to the high face validity associated with ADHD self‐report measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has listed several reasons clients may feign ADHD symptoms, such as to receive testing accommodations (e.g., extra time on exams) or stimulant medications (Booksh, Pella, Singh, & Gouvier, 2010;Sollman, Ranseen, & Berry, 2010). Thus self-report measures, such as the PAI, may be susceptible to efforts to feign ADHD (Musso, Hill, Barker, Pella, & Gouvier, 2016). These previous studies have found that the symptoms of ADHD can be easily feigned, especially when symptoms are assessed with self-report measures (Booksh et al, 2010;Musso et al, 2016;Sollman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts made to detect feigned ADHD have gone beyond self-report measures and clinical interviews to examine the utility of personality inventories (Aita, Sofko, Hill, Musso, & Boettcher, 2017;Butcher, 2009;Morey, 1991;Musso, Hill, Barker, Pella, & Gouvier, 2016;Smith, Cox, Mowle, & Edens, 2017;Young & Gross, 2011), cognitive tests as they are employed in routine neuropsychological examinations (Conners et al, 2000;Fuermaier et al, 2018;Morey, 2016Morey, , 2017Quinn, 2003;Suhr, Sullivan, & Rodriguez, 2011), as well as symptom validity tests developed specifically to uncover feigned cognitive impairment (Edmundson et al, 2017;Fuermaier, Tucha, Koerts, Aschenbrenner, & Tucha, 2017a ;Green, 2003Green, , 2008Leppma, Long, Smith, & Lassiter, 2017) in detecting simulated ADHD. While these efforts have yielded promising results, evidence warranting the use of any single instrument in the detection of aggravated or simulated symptoms is yet lacking.…”
Section: Introductionmentioning
confidence: 99%